A Versatile, Diels–Alder Reaction-Based Approach to Prenyleudesmane Diterpenoids: A Concise Total Synthesis of Sinupol - Ota, Koichiro; Kamaike, Kazuo; Miyaoka, Hiroaki (Synlett, 2020)
Herein, a concise strategy designed to provide general and diversifiable access to various prenyleudesmane terpenoids is described and utilized in the asymmetric synthesis of a biologically active prenyleudesmane diterpenoid, sinupol, which is accomplished in a seven-step procedure.
Keywords: prenyleudesmane diterpenoid; sinupol; PTP1B inhibitor; Diels–Alder reaction; total synthesis